Determination of fat-free mass density and its components in older Hispanic adults by in vivo methods - Rogelio, González-Arellanes; Urquidez Romero, Rene; Rodriguez-Tadeo, Alejandra; Julián, Esparza-Romero; Rosa Olivia, Méndez-Estrada; Erik, Ramírez-López; Alma-Elizabeth, Robles-Sardin; Bertha-Isabel, Pacheco-Moreno; Heliodoro, Alemán-Mateo (2021)
The densitometry method estimates body composition based on cadaver reference values, mainly the fat-free mass density value of 1.100 g/cm3. However, several changes in fat-free mass components by aging, ethnicity, and excess adiposity could influence their density and affect body composition estimations. The present study aimed to compare the mean fat-free mass component values in older Hispanic adults to cadaver reference values. This cross-sectional study included a sample of 420 subjects aged ≥60 yr from northern Mexico. Fat-free mass was determined by the four-compartment model using air displacement plethysmography, the deuterium dilution technique, and dual-energy X-ray absorptiometry for body density, aqueous and mineral fractions of body weight, respectively. A 1-sample t test was used to compare the fat-free mass density and aqueous, mineral, and residue fractions of fat-free mass from subjects in the study to the assumed cadaver reference values. The mean fat-free mass density value for the total sample of older Hispanic adults (1.096 ± 0.011 g/cm3) was significantly (p < 0.001) lower than the assumed value of 1.100 g/cm3, except in obese older men. The mean aqueous fraction of fat-free mass (74.8 ± 3.3%) was higher than the assumed value of 73.8%, and the mean residue fraction of fat-free mass value was lower (18.3 ± 3.4%) than the reference value of 19.4%. Indeed, only the mean mineral fraction of fat-free mass value (6.8 ± 0.8%) was similar to the reference value. In the total sample, all characteristic mean fat-free mass values in these older Hispanic adults differed from cadaver reference values, except the mineral fraction of fat-free mass value.